The efficiency of multiple intelligences strategy in the improvement of attitudes for fourth grade students of basic educational level towards social studies An experimental study in Damascus - Hamdan, Rwaida; Khansa, Abeer (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed at recognizing the efficiency of multiple intelligences strategy in the improvement of attitudes towards social studies for fourth grade students of basic educational level in Damascus City, this study was adopted on experimental approach. The research tool formed of attitude scale designed by the researcher. The population of the research consisted of (177854) fourth- grade basic education students in Damascus. The research sample consisted of (72) male and female students divided into two groups: an experimental group consisted of (34) male and female students of Safia Al-qurashia school studied by multiple intelligences strategy, and a control group consisted of (38) male and female students of the same school studied by traditional manner. The findings of the study were as follows: - The multiple intelligences strategy was effective in the improvement of attitudes towards social studies for fourth grade students of basic educational level. - There were significant statistical differences between the attitudes of experimental group students in the pre and post application of attitude scale, due to multiple intelligences strategy. - There were significant statistical differences between the attitudes of experimental group students and control group students in post application of attitude scale, due to multiple intelligences strategy. Similar studies are suggested for different age stages and studying subjects.